Instrument of Lecturer Performance and Student Activity In the Lecture at Primary School Teacher Education Program - Antonius Edy Setyawan; Nelly Wedyawati; Warkintin Warkintin (Universitas Negeri Makassar, 2018)
The purpose of the study was to develop lecturer performance instruments to measure the ability of lecturers to bring lectures and instruments for student activities while attending the lecture. This study is a research and development (R & D) design developed from the instrument by Rusilowati, which included: (1) needs analysis, (2) determination of indicators and grids, (3) development of questions, (4) expert review, limited trials, field trial (is a cycle activity between review and revision), (5) analysis of trial results and (6) product assembly. The results of the study (1) indicators for lecturer performance instruments were: work ability, initiative in work, work quality, accuracy of work, lecturers’ behavior and appearance, communication and nationalism. (2) indicators for lecture activity instruments: readiness to attend lectures, attendance in lectures and timeliness of completing assignments. (3) the instrument tested on 50 students and lecturers in the Primary School Teacher Education program at STKIP Persada Khatulistiwa Sintang shows that both instruments were valid and reliable. It was concluded that the two instruments can be applied because they were valid and reliable to measure lecturers in bringing lectures and student lecture activities while attending lectures.